2019
DOI: 10.1073/pnas.1916028116
|View full text |Cite
|
Sign up to set email alerts
|

Viral neutralization by antibody-imposed physical disruption

Abstract: In adaptive immunity, organisms produce neutralizing antibodies (nAbs) to eliminate invading pathogens. Here, we explored whether viral neutralization could be attained through the physical disruption of a virus upon nAb binding. We report the neutralization mechanism of a potent nAb 8C11 against the hepatitis E virus (HEV), a nonenveloped positive-sense single-stranded RNA virus associated with abundant acute hepatitis. The 8C11 binding flanks the protrusion spike of the HEV viruslike particles (VLPs) and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
(85 reference statements)
1
13
0
Order By: Relevance
“…The genome of HEV contains three open-reading frames (ORFs), of which ORF2 encodes a major viral capsid protein of 660 amino acids (aa) associated with virion assembly, host interaction, and immunogenicity 15 . The E2s domain (aa 459–606) of the capsid protein forms a homodimer on the virus surface, mediates virus–host interactions, and presents a major target for immune recognition 17 19 . All E2s domains adopt a similar structure 20 , 21 , with an aa-level sequence identity of 83–97% across different genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The genome of HEV contains three open-reading frames (ORFs), of which ORF2 encodes a major viral capsid protein of 660 amino acids (aa) associated with virion assembly, host interaction, and immunogenicity 15 . The E2s domain (aa 459–606) of the capsid protein forms a homodimer on the virus surface, mediates virus–host interactions, and presents a major target for immune recognition 17 19 . All E2s domains adopt a similar structure 20 , 21 , with an aa-level sequence identity of 83–97% across different genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Furthermore, polyphenol extracts are known to activate adenosine monophosphate-activated protein kinase (AMPK), [9] an energy sensor that regulates tight junctions and epithelial permeability. [13] Purple potato is a source of polyphenols. [14] Purple potato extract (PPE) has health beneficial effects, such as antioxidative, [15] antitumor, [16] and antimicrobial [17] activity.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding to viral neutralization mechanism, the established SARS-CoV-2 cross-neutralizing antibody CR3022 provides neutralization through antibody-induced spike disruption 24 . Similarly, we previously showed that the 8C11 antibody can neutralize native Hepatitis E virus (HEV) by antibody-imposed physical disruption 52 . Indeed, although the 7D6/6D6 site is inaccessible for antibody binding to the trimeric spike, 7D6 and 6D6 could still associate with the S-2P protein with excellent a nities (Fig.…”
Section: Discussionmentioning
confidence: 80%